Income aspects of Czech farmers' living conditions - Veronika ANTOŠOVÁ; Naa BIRČIAKOVÁ; Jana STÁVKOVÁ (Agricultural Economics (AGRICECON), 2013)
The paper analyses the income and living conditions of farm households in the Czech Republic. The period under review ware the years of 2005-2010 since more recent data was not available when this paper was being prepared. The primary source of data is the results of the European Union Statistics on Income and Living Conditions (EU SILC) survey. The structure of farm households is established by the household type, education, and economic activity. Households have been assigned to particular groups based on the situation of the household leader. The primary indicator is the average disposable income per 1 equivalent member. Other indicators under review include poverty, poverty depth, and material deprivation. The national poverty line has been defined as 60% of the median average equivalent income. Another important aspect also includes the households' subjective views of the selected matters.